2015
DOI: 10.1111/nyas.12698
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative metabolism of chemical pollutants in marine organisms: molecular and biochemical biomarkers in environmental toxicology

Abstract: Oxidative stress biomarkers are widely used in marine ecotoxicology. Environmental pollutants enhance intracellular formation of oxyradicals through several mechanisms, but complex oxidative interactions occur in response to chemical mixtures. Metabolism of individual classes of pollutants can be influenced by a sophisticated network of prooxidant relationships, reciprocal and cascade effects, changes of redox-sensitive signaling proteins, and transcription factors. Chemically mediated pathways can affect anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 82 publications
(104 reference statements)
1
43
0
2
Order By: Relevance
“…Similar results were also observed in the livers of Carassius auratus injected intraperitoneally with 17 different phthalates at a concentration of 10 mg/kg for 10 days [25]. Many previous studies have shown that oxidative stress status is interrelated with pollutant exposure, which is a possible regulation of the toxicity of these chemicals [52][53][54][55][56][57][58][59].…”
Section: Discussionsupporting
confidence: 78%
“…Similar results were also observed in the livers of Carassius auratus injected intraperitoneally with 17 different phthalates at a concentration of 10 mg/kg for 10 days [25]. Many previous studies have shown that oxidative stress status is interrelated with pollutant exposure, which is a possible regulation of the toxicity of these chemicals [52][53][54][55][56][57][58][59].…”
Section: Discussionsupporting
confidence: 78%
“…Bioaccumulation of pollutants in resident or transplanted organisms is a sure proxy of bioavailability and transfer of chemicals from abiotic matrices to biota, being also recognized in some environmental quality standards. Sub-lethal alterations at molecular and cellular level (biomarkers) provide a sensitive indication of early changes which often represent the first warning signals before the onset of long-term toxicological effects or changes at higher levels of biological organization (Broeg and Lehtonen, 2006;Moore et al, 2006;Regoli and Giuliani, 2014;Benedetti et al, 2015). Various health indices have been described in the last years combining complex biomarker data from multiple cellular pathways, to summarize the severity of biological disturbance in a scientifically sound but also user-friendly format for environmental managers and decision makers (Beliaeff and Burgeot, 2002;Broeg and Lehtonen, 2006;Dagnino et al, 2008;Piva et al, 2011;Benedetti et al, 2012;Marigómez et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the lack of response of MTs in most areas can be attributed to low metal concentrations, even distribution of metals among sites or natural confounding factors (Marigómez et al 2013;Zorita et al 2007) and interactions with other chemicals such as PAHs (Benedetti et al 2015) which could reduce the effect of metals on MT induction.…”
Section: Discussionmentioning
confidence: 70%